Chest wall tuberculosis - A clinical and imaging experience - Grover, Shabnam Bhandari; Jain, Meghna; Dumeer, Shifali; Sirari, Nanda; Bansal, Manish; Badgujar, Deepak (Indian Journal of Radiology and Imaging, 2011)
Aims: Tuberculous infection of the thoracic cage is rare and is difficult to discern clinically or on radiographs. This study aims to describe the common sites and the imaging appearances of chest wall tuberculosis. Materials and Methods: A retrospective review of the clinical and imaging records of 12 confirmed cases of thoracic cage tuberculosis (excluding that of the spine), seen over the last 7 years, was performed. Imaging studies available included radiographs, ultrasonographies (USGs), and computed tomography (CT) scans. Pathological confirmation was obtained in all cases. Results: All patients had clinical signs and symptoms localized to the site of involvement, whether it was the sternum, sternoclavicular joints, or ribs. CT scan revealed sternal destruction in three patients and osteolytic lesions with sclerosis of the articular surfaces of the sternoclavicular joints in two patients. In five patients with rib lesions, USG elegantly demonstrated the bone destruction underlying the cold abscess. All cases were confirmed to be of tuberculous origin by pathology studies of the aspirated/curetted material, obtained by CT / USG guidance. Conclusions: Tuberculous etiology should be considered for patients presenting with atypical sites of skeletal inflammation. CT scan plays an important role in the evaluation of these patients. However, the use of USG for demonstrating rib destruction in a chest wall cold abscess has so far been under-emphasized, as has been the role of CT and USG guided aspiration in confirming the aetiology.
Keywords: Chest wall tuberculosis; radiography; ultrasonography; CT Scan; sternal tuberculosis; sternoclavicular joint tuberculosis; rib tuberculosis; cold abscess